Dinamika Komunikasi Interpersonal Atlet Wushu dalam Menghadapi Tekanan Psikologis pada Fase Pra-Pertandingan - Dhani Reyhan Syahputra; Nur'annafi Farni Syam Maella; Nurul Suhesti; Farida Farida (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze the interpersonal communication dynamics of wushu athletes facing psychological pressure during the pre-competition phase. The analysis rests on a qualitative case study design and DeVito's five dimensions of interpersonal communication. Semi-structured interviews at Sasana Wushu Yasanis Surabaya involved six athletes as key informants, alongside two coaches and two teammates as informants. Thematic analysis covered transcription, repeated reading, initial coding, code grouping, theme development, and interpretation, while source triangulation and member checking strengthened credibility. The findings reveal that athletes' openness is selective, psychological pressure is constructed through personal and relational factors, communication functions ambivalently as both support and a source of pressure, and interpersonal interaction contributes to athletes' emotional co-regulation. The reception of evaluative messages depends on delivery timing, vocal tone, and athletes' emotional state, so the same message can either calm or burden athletes. This study extends interpersonal communication theory into sports communication and provides a practical basis for coaches and club managers to build supportive pre-competition communication.